Self-assembled oxaliplatin(IV) prodrug-porphyrin conjugate for combinational photodynamic therapy and chemotherapy - Lim, Wei Qi (2021)
Nanomedicine has emerged as a promising strategy for effective cancer treatment. A useful approach is to develop carrier-free nanodrugs via a facile supramolecular self-assembly process. To achieve high therapeutic effect, integrating photodynamic therapy with chemotherapy has been sought after. In this work, we designed a nanocarrier (PEG-Por-CD: oxliPt(IV)-ada) assembled with oxaliplatin prodrug (oxliPt(IV)-ada) and porphyrin photosensitizer (PEG-Por-CD) through host-guest interaction to achieve stimulus-responsive combination therapy. Contributed by excellent spatial control of the binding ratio between host and guest molecules, porphyrin and oxaliplatin were separately modified with β-cyclodextrin and adamantane to prepare the amphiphilic host-guest complex for subsequent self-assembly into therapeutic nanoparticles. The obtained PEG-Por-CD: oxliPt(IV)-ada nanoparticles exhibited good colloidal stability with an average hydrodynamic size of 164 nm while undergoing the disassembly under reductive environment to release active therapeutic species. Confocal imaging demonstrated the ability of PEG-Por-CD: oxliPt(IV)-ada to effectively accumulate in the cells and produce reactive oxygen species in vitro upon 630 nm light irradiation. As compared with the monotherapy, the PEG-Por-CD: oxliPt(IV)-ada nanoparticles exhibited 3-fold enhanced cytotoxicity and 2-fold increase in the apoptosis. In vivo experiments using 4T1 tumor-bearing mice confirmed that the nanoparticles were efficient in suppressing the tumor growth without eliciting systemic toxicity. The present self-delivery nanosystem constructed from the self-assembly approach not only allows precise control over the drug and photosensitizer loading ratio but also eliminates systemic toxicity concern of the drug carriers, providing a solution for further development of combinational cancer treatment.